Armoured mud balls revisited - Tanner, Lawrence (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
Armoured mud balls ranging in size from 2 to 20 cm in diameter (long axis) are common in the upper inter-tidal zone around Swan Creek, near Parrsboro, on the north shore of the Minas Basin. Shapes vary from nearly spherical to platy to elongate, with elongate predominant. The mud balls form from the action of wave and tidal currents transporting eroded masses of clay, as evidenced by the strike- and dip-parallel orientations of the mud balls with respect to the shore.